2017
DOI: 10.1016/j.celrep.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Tail-Anchored Protein Insertion by a Single Get1/2 Heterodimer

Abstract: SUMMARY The Get1/2 transmembrane complex drives the insertion of tail-anchored proteins from the cytosolic chaperone Get3 into the endoplasmic reticulum membrane. Mechanistic insight into how Get1/2 coordinates this process is confounded by a lack of understanding of the basic architecture of the complex. Here we define the oligomeric state of full-length Get1/2 in reconstituted lipid bilayers by combining single-molecule and bulk fluorescence measurements with quantitative in vitro insertion analysis. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…They were originally identified as a putative receptor for the targeting factor Get3 based on genetic and physical interaction studies in budding yeast [45], and then demonstrated in reconstitution studies with recombinant factors to constitute the minimal insertion machinery [117]. Single-molecule analysis suggests that a single Get1/2 heterodimer is sufficient for insertion of tail-anchored proteins into the lipid bilayer [118].…”
Section: The Sec Translocation Channelmentioning
confidence: 99%
“…They were originally identified as a putative receptor for the targeting factor Get3 based on genetic and physical interaction studies in budding yeast [45], and then demonstrated in reconstitution studies with recombinant factors to constitute the minimal insertion machinery [117]. Single-molecule analysis suggests that a single Get1/2 heterodimer is sufficient for insertion of tail-anchored proteins into the lipid bilayer [118].…”
Section: The Sec Translocation Channelmentioning
confidence: 99%
“…After a TA protein is loaded onto Get3, the complex is targeted to the Get1/2 transmembrane complex at the ER [9,4446]. Although early models proposed that Get1/2 might function as a heterotetramer [44,45], it is now clear that a Get1/2 heterodimer, comprising a single copy of each subunit, is both necessary and sufficient for TA targeting and insertion [47]. Get1 and Get2 (WRB and CAML in humans) [4850] each contain three predicted TMDs through which the two subunits associate, and large cytosolic-facing domains containing conserved residues that mediate binding to Get3.…”
Section: Events At the Membranementioning
confidence: 99%
“…Fully closed conformations (e.g., Get3-TA-ATP) do not bind with high affinity to Get1. However, in the presence of Get2, Get1 is able to interact with loose, ADP-bound states of Get3 [47]. The dynamic nature of this conformation leads to formation of a tight complex between Get1 and nucleotide-free Get3 that drives TA protein release [38,39,4446].…”
Section: Events At the Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Get1/Get2 and WRB/CAML form the minimal machinery required for TA protein membrane insertion (Vilardi et al, 2014;Wang et al, 2011;Yamamoto and Sakisaka, 2012;Zalisko et al, 2017). Although their TMDs provide a membrane-integrated docking site for the TA substrate (Wang et al, 2014), it is unknown how Get1/Get2 act as a membrane insertase in the absence of a structure of the complex.…”
Section: Introductionmentioning
confidence: 99%